Application program for DICOM file handling - Huang, Zheng Lin. (2008)
This thesis consists of 2 parts. -Part B-. DICOM (Digital Imaging and Communications in Medicine) is the industry standard for transferal of radiological images and other medical information between computers. It enables users to retrieve images and associated information from digital imaging equipment in a standard format that would be the same across multiple manufacturers. Since it was created by the National Electrical Manufacturers Association (NEMA), the DICOM standard has become the predominant standard for the communication of medical images.